Sex differences in discriminating between cues predicting threat and safety - Day, Harriet L.; Reed, Molly M.; Stevenson, Carl W. (Elsevier, 2016)
Post-traumatic stress disorder (PTSD) is more prevalent in women than men. PTSD is characterized by overgeneralization of fear to innocuous stimuli and involves impaired inhibition of learned fear by cues that predict safety. While evidence indicates that learned fear inhibition through extinction differs in males and females, less is known about sex differences in fear discrimination and safety learning. Here we examined auditory fear discrimination in male and female rats. In Experiment 1A, rats underwent 1-3 days of discrimination training consisting of one tone predicting threat (CS+; presented with footshock) and another tone predicting safety (CS-; presented alone). Females, but not males, discriminated between the CS+ and CS- after one day of training. After 2-3 days of training, however, males discriminated whereas females generalized between the CS+ and CS-. In Experiment 1B, females showed enhanced anxiety-like behaviour and locomotor activity in the open field, although these results were unlikely to explain the sex differences in fear discrimination. In Experiment 2, we found no differences in shock sensitivity between males and females. In Experiment 3, males and females again discriminated and generalized, respectively, after three days of training. Moreover, fear generalization in females resulted from impaired safety learning, as shown by a retardation test. Whereas subsequent fear conditioning to the previous CS- retarded learning in males, females showed no such retardation. These results suggest that, while females show fear discrimination with limited training, they show fear generalization with extended training due to impaired safety learning.